FEMALE LEADERSHIP AND SOCIAL WELFARE POLICY: Case studies from three regions in Indonesia (Surabaya, Kutai Kertanegara and South Minahasa) - Longgina Novadona Bayo (Program Magister Ilmu Politik, Universitas Diponegoro, 2018)
After the fall of Soeharto Regime in 1998, the Reform Era in Indonesia began by promoted freedom and autonomy. The centralized approach based on the New Order’s Act No. 5/1974 was replaced by the Act No. 22/1999 on Local Government Autonomy by gave considerable authority to regencies (kabupaten) and municipalities (kota or kotamadya). Some of the scholars labelled the Act No. 22/1999 as “one of the most radical decentralization programs attempted anywhere in the world” (Aspinall 2003: 3). Several years later Act No. 22/1999 was replaced by Act No. 32/2004. Some scholars have suggested that Act No. 32/2004 indicates “recentralization” in the sense that it strengthens the central government by giving it a degree of control over administrative and ﬁscal matters (Pratikno 2009: 57; Buehler 2009: 102). However, the significant point in the Act No. 32/2004 which introduced direct local head election mechanism for electing local government head was the structural opportunities for women to take greater leadership in local politics. As result, the direct local election from 2005 until 2017 demonstrates the trend of increasing number female political leaders elected as governors/regents/mayors in local politics in post-Suharto.